Brain Responses to Emotional Faces in Natural Settings: A Wireless Mobile EEG Recording Study - Soto, Vicente; Tyson-Carr, John; Kokmotou, Katerina; Roberts, Hannah; Cook, Stephanie; Fallon, Nicholas; Giesbrecht, Timo; Stancak, Andrej (Frontiers in Psychology, 2018)
Detection of human face in a visual field and correct reading of emotional expression of faces are important elements in everyday social interactions, decision making and emotional responses. Although brain correlates of face processing have been established in previous fMRI and EEG/MEG studies, little is known about brain representation of faces and emotional expressions of faces in freely moving humans. The present study aimed at detection of brain electrical potentials during viewing human faces in natural settings. A 64-channel wireless EEG and eye-tracking data were recorded in 19 participants while they moved in a mock art gallery and stopped at times to evaluate pictures hung on the walls. Positive, negative and neutral valence pictures of objects and human faces which were displayed. The time instants in which pictures first occurred in the visual field were identified in eye-tracking data and used to reconstruct the triggers in continuous EEG data after synchronising the time axes of the EEG and eye-tracking device. EEG data showed a clear face-related event-related potential (ERP) in the latency interval ranging from 165 to 210 ms (N170); this component was not seen whilst participants were viewing non-living objects. The face ERP component was stronger during viewing disgusted compared to neutral faces. Source dipole analysis revealed an equivalent current dipole in the right fusiform gyrus (BA37) accounting for N170 potential. Our study demonstrates for the first time the possibility of recording brain responses to human faces and emotional expressions in natural settings. This finding opens new possibilities in clinical, developmental, social, forensic, or marketing research in which information about face processing is of importance.